Esophageal neuroendocrine carcinoma: A clinical perspective on a rare and challenging disease - Benayad Aourarh; Aziz Aourarh; Lina Belkouchi; Rachida Saouab; Mohamed Amine Essaoudi (Radiology Case Reports)
Neuroendocrine carcinomas (NECs) of the esophagus are exceptionally rare, comprising only 0.04% of all neuroendocrine tumors. These malignancies can remain asymptomatic or manifest through digestive symptoms such as dysphagia and abdominal discomfort. Due to their rarity, limited studies exist, resulting in insufficient knowledge about their prognosis and treatment, with conflicting data in the literature.This report presents the case of a 62-year-old male chronic smoker with chronic dysphagia. Diagnostic evaluations, including gastroscopy and CT, revealed a circumferential lesion in the lower esophagus. Histopathological analysis confirmed a diagnosis of poorly differentiated large-cell neuroendocrine carcinoma.Esophageal NECs are aggressive and poorly understood tumors. Tumor size, lymph node involvement, and metastatic status are critical factors influencing treatment decisions. However, there are no established guidelines for their management. Extensive research is urgently needed to develop standardized treatment approaches and improve the prognosis of patients with high-grade esophageal NECs.